Normal intellectual ability and hyperprolactinemia as unique clinical manifestations of congenital hypothyroidism: A case report and review of hypotheses - Zulfa, Putri O.; Debbyousha, Maulina; Sucipto, Krishna W.; Ekadamayanti, Agustia S.; Firdausa, Sarah; Zufry, Hendra (Narra J, 2023)
Congenital hypothyroidism is the deficiency of thyroid hormone in infants and hyperprolactinemia is frequently observed. Previously reported cases typically involve intellectual disability, highlighting this particular unique case report to the first reported patient demonstrating normal intellectual ability despite experiencing growth and gonad dysfunction. This study aims to present a case and review medical hypotheses related to the patient's condition. A 19-year-old female presented with a chief complaint of irregular menstruation for up to 40 days or not occurring at all. The patient experienced the first menstruation at the age of 16 years old. The patient's height was 133 cm, body weight 40 kg, and body mass index 22.61 kg/m2; other family members were normal. Physical examination showed no abnormalities, and laboratory examination showed suppressed serum free T4 (FT4) level (6.41 pmol/L), elevated thyroid stimulating hormone (TSH) level (333.700 µIU/mL), and elevated prolactin hormone level (32.03 ng/mL). Ultrasound of the thyroid gland found hypoplasia of the left and right thyroid glands. The patient was a college student enrolled in a public national university and had never complained about academic performance throughout the patient's education. The patient was diagnosed with congenital hypothyroidism and hyperprolactinemia. The patient was administered up to 100 μg daily of oral levothyroxine, which improved the patient’s menstrual cycles. The patient's delayed diagnosis may be attributed to central congenital hypothyroidism being underdiagnosed. We hypothesized that thyroid-releasing hormone receptor (TRHR) gene mutation might contribute to the underlying cause of hyperprolactinemia and normal intellectual ability of the patient. Further study on the significance of TRHR gene mutations in congenital hypothyroidism is required to improve diagnosis and treatment.